2018
DOI: 10.1016/j.scitotenv.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Removal of TiO2 nanoparticles from water by low pressure pilot plant filtration

Abstract: Rising use of nanoparticles in manufacturing as well as in commercial products bring issues related to environmental release and human exposure. A large amount of TiO nanoparticles will eventually reach wastewater treatment plants. Low pressure membrane filtration has been suggested as a feasible treatment of water streams. This study investigated first at laboratory scale the influence of: i) membrane material, ii) pore size and iii) water chemistry on nTiO removal. TiO retention was governed by the cake laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This reduced flux was consistent with the decreased porosity for AZO membranes (61 ± 2% for AZO25, 57 ± 3% for AZO37, and 43 ± 3% for AZO25) compared to the plain 0.22 μm PVDF membrane (75 ± 4%) (Figure S3). The fluxes of AZO membranes were still above the recommended filtration flux of 50–100 LMH for typical microfiltration conditions so that the membranes were not operated at the maximum flux to avoid severe fouling and more frequent cleaning …”
Section: Resultsmentioning
confidence: 99%
“…This reduced flux was consistent with the decreased porosity for AZO membranes (61 ± 2% for AZO25, 57 ± 3% for AZO37, and 43 ± 3% for AZO25) compared to the plain 0.22 μm PVDF membrane (75 ± 4%) (Figure S3). The fluxes of AZO membranes were still above the recommended filtration flux of 50–100 LMH for typical microfiltration conditions so that the membranes were not operated at the maximum flux to avoid severe fouling and more frequent cleaning …”
Section: Resultsmentioning
confidence: 99%
“…Likewise, during the use of nano-TiO2 in aqueous systems, a combination of humic acid and HCO3increased the release of Ti in water. Olabarrieta et al (2018) reported that the nano-TiO2 rejection rate was generally above 95% in a low-pressure membrane filtration pilot plant, and 2.3 g of the NPs could be released when treating 31 m 3 of tap water with 2 mg/L nano-TiO2.…”
Section: Environmental Risk Of Nanomaterialsmentioning
confidence: 99%
“…NPs have become a part of modern life. NPs have been used in various industrial processes and commercial products such as cosmetics, coatings, construction, and environmental remediation [27,28]. These NPs can be used as adsorbents for contact with metallic species [29] since they provide substantial binding sites for interaction [30].…”
Section: Introductionmentioning
confidence: 99%